2008
DOI: 10.1128/aac.01208-07
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of a Hepatitis C Virus (HCV) NS4A Antagonist in Combination with HCV Protease and Polymerase Inhibitors

Abstract: Rapid emergence of resistance to monotherapy with virus-specific inhibitors necessitates combination therapy. ACH-806 is a hepatitis C virus NS4A inhibitor with a novel mechanism of action and resistance pathway. This compound was synergistic with NS3 protease inhibitors and NS5B nucleoside and nonnucleoside polymerase inhibitors.Significant progress has been made in the discovery and testing of novel inhibitors of hepatitis C virus (HCV) replication (4). The majority of the compounds evaluated in vitro and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…More importantly, no antagonistic antiviral effects or enhanced cytotoxicity was observed in any of these combinations. Although the EC 50 (55.2 IU/ml) of IFN-␣ for stable HCV1b replicon cells was higher than the values reported by other groups (Table 4) (34,35,39,59), the EC 50 of IFN-␣ for our parental HCV1b replicon measured by transient HCV1b replicon assay was in the region of 3 IU/ml (data not shown), comparable to most of the values reported by others. Moreover, several mutations within the C terminus of NS5A were identified by sequencing analysis of cDNAs derived from viral RNAs of our stable HCV replicon cells compared to the sequences of parental HCV1b replicon plasmid for transient replicon assay (data not shown).…”
Section: Fig 4 Pharmacokinetics Of Bp008 After Intravenous (Iv) or Orsupporting
confidence: 38%
“…More importantly, no antagonistic antiviral effects or enhanced cytotoxicity was observed in any of these combinations. Although the EC 50 (55.2 IU/ml) of IFN-␣ for stable HCV1b replicon cells was higher than the values reported by other groups (Table 4) (34,35,39,59), the EC 50 of IFN-␣ for our parental HCV1b replicon measured by transient HCV1b replicon assay was in the region of 3 IU/ml (data not shown), comparable to most of the values reported by others. Moreover, several mutations within the C terminus of NS5A were identified by sequencing analysis of cDNAs derived from viral RNAs of our stable HCV replicon cells compared to the sequences of parental HCV1b replicon plasmid for transient replicon assay (data not shown).…”
Section: Fig 4 Pharmacokinetics Of Bp008 After Intravenous (Iv) or Orsupporting
confidence: 38%
“…Given the limited efficacy of ACH-806 in the applied assay, calculation of the EC 50 was not possible for all treatments done; overall determinable EC 50 s were in the range of 1,000 to 10,000 nM, thus being several orders of magnitude higher than EC 50 values determined in genotype 1 replicon systems (11)(12)(13). EC 50 values strongly depend on the assay used.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, the first two directly acting antivirals targeting HCV NS3P, telaprevir and boceprevir, were licensed for treatment of chronic genotype 1 infection (10). Several other protease inhibitors are advanced in clinical trials, while inhibitors of HCV NS4A are in preclinical development (10)(11)(12)(13). We and others have reported that HCV recombinants with genotype-specific NS3P/NS4A show differential responses to protease inhibitors (14)(15)(16).…”
mentioning
confidence: 99%
“…NS3/4A protease inhibitors have previously been shown to demonstrate synergy with agents acting via multiple other mechanisms, including peginterferon alfa 2a (20,45), NS5B polymerase inhibitors (7,14), NS4A antagonists (53), and cyclosporine analogs (3,30). In the short term, they may allow a reduced duration of therapy when they are used in combination with interferon and ribavirin, coupled with improved SVR rates, particularly in difficult-to-treat genotype 1-infected patients.…”
Section: Discussionmentioning
confidence: 99%